CAUSES OF THE ORIGIN OF OSTEOCHONDROSIS, SYMPTOMS, DIAGNOSIS AND TREATMENT METHODS (Conferencea, 2022)
Osteochondrosis is a disease of the spine. In folk language, it is also called a disease of salt accumulation between the joints. We often find diagnoses that the lumbar spine and cervical vertebrae are osteochondrosis .